ACTOPOLIS - The art of action = ACTOPOLIS - Die Kunst zu handeln - Fitz, Angelika 1967-; Aßmann, Katja 1971-; Fritz, Martin 1977- (Jovis, 2017)
Cities today face challenges all over the world. How is it possible to expand and preserve urban space as a common area of society even in times of its economic exploitation and privatisation? What is the role of art, culture, architecture, self-organised action and activism in these processes? Over the past few years artists, architects, philosophers, urbanists, and activists have been working on these questions in seven different European cities—Ankara/Mardin, Athens, Belgrade, Bucharest, Oberhausen, Sarajevo and Zagreb—within the framework of the international project ACTOPOLIS: The Art of Action. ACTOPOLIS is a call to action and to co-author the city—across disciplines, national boundaries, and cultural differences.